1998
DOI: 10.1103/physrevlett.81.995
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Laser Wakefield Acceleration of Electrons

Abstract: The acceleration of electrons injected in a plasma wave generated by the laser wake eld mechanism has been observed. A maximum energy gain of 1.6 MeV has been measured and the maximum longitudinal electric eld is estimated to 1.5 GV/m. The experimental data agree with theoretical predictions when 3D e ects are taken into account. The duration of the plasma wave inferred from the number of accelerated electrons is of the order of 1 ps. 41.75. Lx,52.40.Nk Typeset using REVT E X 1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
117
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 222 publications
(119 citation statements)
references
References 22 publications
0
117
0
2
Order By: Relevance
“…Electrons from a conventional accelerator can be injected into the wakefield, but matching the beam properties to the wakefield size is difficult leading to low efficiency of particle trapping [32]. A number of advanced techniques have been proposed and demonstrated that use density modification [33][34][35], secondary laser beams [36][37][38] or ionization [39][40][41] to greatly simplify injection into the wakefield.…”
Section: Laser Wakefield Accelerationmentioning
confidence: 99%
“…Electrons from a conventional accelerator can be injected into the wakefield, but matching the beam properties to the wakefield size is difficult leading to low efficiency of particle trapping [32]. A number of advanced techniques have been proposed and demonstrated that use density modification [33][34][35], secondary laser beams [36][37][38] or ionization [39][40][41] to greatly simplify injection into the wakefield.…”
Section: Laser Wakefield Accelerationmentioning
confidence: 99%
“…[47][48][49][50]. On the second step this electron beam collides head on with the same focused laser beam (so that the effect of the magnetic field is negligible and F < 0).…”
Section: Pair Creation Using An E144 Analogous Scheme: E + E − Casementioning
confidence: 99%
“…To achieve these values, an XFEL laser beam ofhω = 100 eV, can be used to produce and accelerate an electron beam (as is described in Refs. [47][48][49][50]) which collides head on with the same focused XFEL laser beam. Again in the electron's frame of reference, photon energy will transform tohω * = γ Lh ω where the Lorentz factor is γ L = E e-beam /mc 2 .…”
Section: Pair Creation Using An E144 Analogous Scheme: E + E − Casementioning
confidence: 99%
“…Demonstration experiments at LLNL should follow shortly. In addition, we plan to study the issues associated with handling of higher power picosecond laser sources in this device, such as are found in laser-scattering and laser wake-field accelerator experiments [11].…”
Section: Rf Waveformmentioning
confidence: 99%